Infection of Human Monocytes with Leishmania infantum Strains Induces a Downmodulated Response when Compared with Infection with Leishmania braziliensis - Viana, Agostinho Gonçalves; Magalhães, Luísa Mourão Dias; Giunchetti, Rodolfo Cordeiro; Dutra, Walderez O.; Gollob, Kenneth J. (Frontiers in Immunology, 2018)
Human infection with different species of Leishmania leads to distinct clinical manifestations, ranging from relatively mild cutaneous (Leishmania braziliensis) to severe visceral (Leishmania infantum) forms of leishmaniasis. Here, we asked if in vitro infection of human monocytes by Leishmania strains responsible for distinct clinical manifestations leads to early changes in immunological characteristics and ability of the host cells to control Leishmania. We evaluated the expression of toll-like receptors and MHC class II molecules, cytokines, and Leishmania control by human monocytes following short-term infection with L. braziliensis (M2904), a reference strain of L. infantum (BH46), and a wild strain of L. infantum (wild). The induction of TLR2, TLR9 and HLA-DR were all lower in L. infantum as compared to L. braziliensis infected cells. Moreover, L. infantum infected monocytes (both strains) produced lower TNF-alpha and a lower TNF-alpha/IL-10 ratio, resulting in a weaker inflammatory profile and a 100 fold less effective control of Leishmania than cells infected with L. braziliensis. Our results show that L. infantum strains fail to induce a strong inflammatory response, less activation, and less control of Leishmania from human monocytes, as compared to that induced by L. braziliensis infection. This functional profile may help explain the distinct clinical course observed in patients infected with the different Leishmania species.